Assessment of Health, Nutrition Status, Lifestyle Patterns, Job Satisfaction Level, and Sanitation Practices of Food Handlers Working in University Residential Hall’s Canteens of Bangladesh - Hossain, Md Sabbir; Prattay, Kazi Milenur Rahman; Alif, Al Ashiqur Rahman; Shipa, Sowkat Jahan; Sarkar, Md Raihan; Karim, Md Rasul (Dhaka University Journal of Pharmaceutical Sciences, 2024)
In Bangladesh, a notable number of people are engaged in food handling (preparing, serving and selling) jobs. Their dietary habits, lifestyle patterns and other behavioral factors are somewhat descending. The study aimed to identify the health status, nutrition status, lifestyle patterns, job satisfaction level and sanitation practices of food handlers working in student residential hall’s canteens and messes at the University of Dhaka, Bangladesh. Data was collected through direct physical measurement and a standard questionnaire, which was translated into Bengali for ease of data collection. It was structured by focusing on data related to socio-demographics, dietary habits, awareness level of food and nutrition, lifestyle patterns, current job satisfaction level, family history and sanitation practice. Among the study participants, 11.0%, 8.7% and 2.0% of them were overweight, underweight, and obese, respectively. The study found that the BMI status of the food handlers was significantly associated with their age (χ2 = 42.796, P < 0.001). 42.7% of participants had poor dietary habits (χ2 = 2.586, P = 0.460), and half of the participants (50.7%) lifestyles were poor (χ2 = 4.626, P = 0.201). Only 27.0% of participants were aware of the health risks associated with poor dietary habits and malnutrition. 83.0% of the participants were habituated to wearing shoes while doing their duty. 84.7% had access to hygienic bathroom and toilet facilities. 37.7% of study participants did not participate in regular outdoor physical activities. Only 46.3% of participants were satisfied with their job. A number of food handlers were found to be malnourished and experienced unfavorable health conditions. The associated authority should take it into consideration for the improvement of overall nutritional health status, lifestyle patterns, and overall, the job environment. Dhaka Univ. J. Pharm. Sci. 23(2): 145-155, 2024 (December)